In vivo Activity of Copper(II), Manganese(II), and Silver(I) 1,10-Phenanthroline Chelates Against Candida haemulonii Using the Galleria mellonella Model - Gandra, Rafael M.; McCarron, Pauraic; Viganor, Livia; Fernandes, Mariana Farias; Kavanagh, Kevin; McCann, Malachy; Branquinha, Marta H.; Santos, André L. S.; Howe, Orla; Devereux, Michael (Frontiers in Microbiology, 2020)
Candida haemulonii is an emerging opportunistic pathogen resistant to most antifungal drugs currently used in clinical arena. Metal complexes containing 1,10-phenanthroline (phen) chelating ligands have well-established anti-Candida activity against different medically relevant species. This study utilized larvae of Galleria mellonella, a widely used model of in vivo infection, to examine C. haemulonii infection characteristics in response to different copper(II), manganese(II) and silver(I) chelates containing phen, which had demonstrated potent anti-C. haemulonii activity in a previous study. The results showed that C. haemulonii virulence was influenced by inoculum size and incubation temperature, and the host G. mellonella immune response was triggered in an inoculum-dependent manner reflected by the number of circulating immune cells (haemocytes) and observance of larval melanization process. All test chelates were non-toxic to the host in concentrations up to 10 µg/larva. The complexes also affected the G. mellonella immune system, affecting the haemocyte number and the expression of genes encoding antifungal and immune-related peptides (e.g. inducible metalloproteinase inhibitor protein, transferrin, galiomycin and gallerimycin). Except for [Ag2(3,6,9-tdda)(phen)4].EtOH (3,6,9-tddaH2= 3,6,9-trioxoundecanedioic acid), all chelates were capable of affecting the fungal burden of infected larvae and the virulence of C. haemulonii in a dose-dependent manner. This work shows that copper(II), manganese(II) and silver(I) chelates containing phen with anti-C. haemulonii activity are capable of (i) inhibiting fungal proliferation during in vivo infection, (ii) priming an immune response in the G. mellonella host and (iii) affecting C. haemulonii virulence.